Liquidity coinsurance and bank capital - Fabio Castiglionesi; Fabio Feriozzi; Gyöngyi Lóránth; Loriana Pelizzon (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
Banks can deal with their liquidity risk by holding liquid assets (self-insurance), by participating in interbank markets (coinsurance), or by using flexible financing instruments, such as bank capital (risk-sharing). We use a simple model to show that undiversi fiable liquidity risk, i.e. the liquidity risk that banks are unable to coinsure on interbank markets, represents an important risk factor affecting their capital structures. Banks facing higher undiversi fiable liquidity risk hold more capital. We posit that empirically banks that are more exposed to undiversifi able liquidity risk are less active on interbank markets. Therefore, we test for the existence of a negative relationship between bank capital and interbank market activity and find support in a large sample of U.S. commercial banks.
Keywords: G21; 330; Bank Capital; Interbank Markets; Liquidity Coinsurance